Research landscape and trends of cerebral amyloid angiopathy: a 25-year scientometric analysis - Wang, Kunyu; Zhang, Beilin; Du, Heqian; Duan, Hanying; Jiang, Zhuoya; Fang, Shaokuan (Frontiers in Neurology, 2024)
Background Cerebral amyloid angiopathy (CAA), a cerebral small vessel disease affecting leptomeningeal and cortical small blood vessels, is a common cause of spontaneous lobar intracerebral hemorrhage and cognitive impairment, particularly in elderly patients. This study aims to investigate the field of CAA research from a scientometric perspective. Methods Publications related to CAA from January 1st, 1999 to September 29th, 2023 were retrieved from the Web of Science Core Collection database. The scientometric software VOSviewer and CiteSpace were used to analyze and visualize the publication trends, countries/regions, institutions, authors, journals, cited references, and keywords of CAA. Results A total of 2,798 publications related to CAA from 73 countries/regions, led by the United States, were included. The number of publications showed an increasing trend over time. Massachusetts General Hospital was the most productive institution, and authors Greenberg and Charidimou published the most papers and were most frequently co-cited. Journal of Alzheimer's Disease was the most prolific journal in this field, and Neurology was the most co-cited journal. Apart from “cerebral amyloid angiopathy”, the most frequently used keywords were “Alzheimer's disease”, “amyloid beta”, “intracerebral hemorrhage”, and “dementia”. The burst keywords in recent years included “cortical superficial siderosis” and “dysfunction”. Conclusions This scientometric analysis provides a comprehensive overview of CAA research over the past 25 years, and offers important insights for future research directions and scientific decision-making in this field.